Avaliação da reação de acessos de melancia para fitonematoides Meloidogyne enterolobii - Costa Filho, José Hamilton da (2012)
Considering the economic importance of the watermelon for the State of Rio Grande do Norte and the high cost of chemical control of root-knot nematodes, to whose species only few crops, including watermelon, have been evaluated so far, it is necessary to carry out research in order to identify watermelon genotypes resistant to Meloidogyne enterolobii since this species was found in field crop production of Assu- Mossoro. An experiment was carried out at Embrapa Semiarid in the county of Petrolina-PE with the objective to evaluate the reaction of 20 watermelon accessions, collected in the State of Rio Grande do Norte, to Meloidogyne enterolobii. The experimental design was a completely randomized block with 20 accession treatments and ten replications. Each experimental unit was one pot containing three liters of sterilized substract with one watermelon plant. A suspension of 2,200 root-knot nematodes was applied to each pot at four days of transplantation. The variables recorded, for each plant, were root mass (g), number of galls (NG), number of egg masses (NEM), number of eggs (NE) and factor of reproduction (FR). The statistical data analysis was performed using the software SISVAR and the means were compared using Tukey at 5% of significance (p < 0.05) for the variables NG, NEM and NE, and Scott-Knott at the same level of significance for FR. There was great variation in response among the watermelon accessions for the recorded variables. However, there was no correlation between any pair of analyzed variable, except the correlation of number of eggs and factor of reproduction. Moreover, considering the average per accession for the variables NG and FR all of them were susceptible. However, when the variation within each accession was analyzed, some accessions presented some plants with FR < 1.0 (02, 07, 09, 10 and 13), indicating variation for this character. The accessions 9 and 10 presented, respectively, 40 and 30% of plants with FR < 1.0, which indicates that they are promising to be used in a breeding program to obtain homozygous source of resistance to Meloidogyne enterolobii and, therefore, there is genetic variability for this character in the watermelon accessions collected in the State of Rio Grande do Norte.